2015
DOI: 10.1080/10406638.2014.984857
|View full text |Cite
|
Sign up to set email alerts
|

Priority Polycyclic Aromatic Hydrocarbons (PAHs): Distribution, Possible Sources and Toxicity Equivalency in Urban Drains

Abstract: Wastewater from urban areas constitutes one of the major sources of pollutants contributed to aquatic ecosystem. This study was carried out to elucidate the occurrence and possible source of US Environmental Protection Agency identified 16 priority polycyclic aromatic hydrocarbons (PAHs) in water and sediments from the urban wastewater drains in Delhi, India. A total 60 samples (water and sediment) collected during year 2011-2012, and analyzed the following USEPA methods. Water and sediment samples were extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…This point was demonstrated using mass fractions analysis and is further supported by simply comparing PAH concentrations from the present study with concentrations in areas where coal‐tar sealants are not used (i.e., outside of the eastern and central United States and Canada). Compared with a ΣPAH 16 mean of 13 300 µg/kg and maximum of 196 000 µg/kg for the present study, studies of urban streams, canals, drains, and lakes in Portland (OR, USA; Yanagida et al 2012), Sydney (Australia; Nguyen et al 2014), Delhi (India; Kumar et al 2016), Beijing (China; Shen et al 2009), Shanghai (China; Yang et al 2018), and Bangkok (Thailand; Boonyatumanond et al 2006) reported mean ΣPAH 16+ concentrations of 663 to 5570 µg/kg (Figure 9). The maximum ΣPAH 16+ concentrations in these studies were all <9000 µg/kg, with the exception of Delhi storm drain sediments, which had a maximum of 19 300 µg/kg.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…This point was demonstrated using mass fractions analysis and is further supported by simply comparing PAH concentrations from the present study with concentrations in areas where coal‐tar sealants are not used (i.e., outside of the eastern and central United States and Canada). Compared with a ΣPAH 16 mean of 13 300 µg/kg and maximum of 196 000 µg/kg for the present study, studies of urban streams, canals, drains, and lakes in Portland (OR, USA; Yanagida et al 2012), Sydney (Australia; Nguyen et al 2014), Delhi (India; Kumar et al 2016), Beijing (China; Shen et al 2009), Shanghai (China; Yang et al 2018), and Bangkok (Thailand; Boonyatumanond et al 2006) reported mean ΣPAH 16+ concentrations of 663 to 5570 µg/kg (Figure 9). The maximum ΣPAH 16+ concentrations in these studies were all <9000 µg/kg, with the exception of Delhi storm drain sediments, which had a maximum of 19 300 µg/kg.…”
Section: Discussionmentioning
confidence: 61%
“…bar = mean; whisker = maximum. a Kumar et al 2016; b Shen et al 2009; c Boonyatumanond et al 2006; d Nguyen et al 2014; e Yang et al 2018; f Yanagida et al 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Te existence of diferent homologs of PAHs (PAHs with a number of aromatic rings) and PAHs with diferent molecular weights in the environment suggests their likely origin or sources [72][73][74][75][76][77].…”
Section: Source Apportionmentmentioning
confidence: 99%